The role of HRM-service quality in the relationship between electronic human resource management and perceived performance - Mariah El Saeed; Heba Mohamed Maarouf; Raghda Abulsaoud Ahmed Younis (Future Business Journal)
Abstract Purpose This research aims to examine how electronic human resource management (E-HRM) impacts perceived organizational performance (OP) and job performance (JP) in telecommunications organizations, with a particular emphasis on the mediating effect of HR service quality (HRSQ). Research methodology A questionnaire was developed based on a validated process. Data were collected from 430 employees among the telecommunication companies. However, only 400 questionnaires were valid for the statistical analysis. We use smart PLS and structural equation modeling using Smart PLS v3.2.2 to examine the direct and indirect relationships. Results and findings The results of this research revealed that E-HRM has a direct, significant, and positive impact on perceived job performance, as well as organizational performance. Moreover, HRSQ significantly mediates the relationships between E-HRM and job and organizational performance. Empirical implications The research introduces empirical several consequences that are discussed later in this paper. The results highlight the importance of designing and implementing E-HRM systems that support organizational workflow and allow employees to do a variety of tasks more efficiently. Originality Existing research has shown a link between e-HRM and HR service quality; nonetheless, these studies highlight e-HRM’s potential impact on perceived performance, at both the job and organizational performance levels. The study contributes to the HRM literature by identifying how E-HRM might boost perceived performance by improving HR service quality. As a result, the study serves as a foundation for future theoretical developments in this field.